2018
DOI: 10.1017/s1742170517000783
|View full text |Cite
|
Sign up to set email alerts
|

Farm service agency employee intentions to use weather and climate data in professional services

Abstract: Agricultural service providers often work closely with producers, and are well positioned to include weather and climate change information in the services they provide. By doing so, they can help producers reduce risks due to climate variability and change. A national survey of United States Department of Agriculture Farm Service Agency (FSA) field staff (n = 4621) was conducted in 2016. The survey was designed to assess FSA employees’ use of climate and weather-related data and explore their perspectives on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 56 publications
1
5
1
Order By: Relevance
“…This aligns with previous research that found that Midwestern farmers' current use of conservation practices, also categorized as adaptation BMPs, are a good indicator of what farmers intend on doing in the future [15]. However, other research suggests that historical behavior is not always the most important indicator of behavioral intentions or realized behavioral change [66,67].…”
Section: Discussionsupporting
confidence: 87%
“…This aligns with previous research that found that Midwestern farmers' current use of conservation practices, also categorized as adaptation BMPs, are a good indicator of what farmers intend on doing in the future [15]. However, other research suggests that historical behavior is not always the most important indicator of behavioral intentions or realized behavioral change [66,67].…”
Section: Discussionsupporting
confidence: 87%
“…First, a sizable proportion of farmers have already adopted climate-mitigative practices. They are motivated to do so for many reasons, but neither agreement with climate science, nor an ascription of responsibility for mitigation, are among the motivators, a finding that departs from several other studies identifying climate change beliefs as a strong predictor of adoption [9,29,41] (beliefs that climate change is human caused have been found to be relatively less significant in studies of adaptation behaviours [47]). Rather, farmers recognize numerous co-benefits of mitigative practices, such as soil quality improvement, and wildlife and biodiversity enhancement.…”
Section: Discussioncontrasting
confidence: 58%
“…These reported beliefs in climate change were higher than among similar studies of farmers conducted in other parts of the USA (Prokopy et al ., 2015; Chatrchyan et al ., 2017). Additionally, previous research makes a connection between these climate beliefs and support for climate action (Howden et al ., 2007; Arbuckle et al ., 2013; Hyland et al ., 2016; Chatrchyan et al ., 2017) suggesting that as belief in anthropogenic climate change increases, so does support for adaptive and mitigative action, although this trend is not always supported in the literature (Schattman et al ., 2018 a , 2018 b ).…”
Section: Resultsmentioning
confidence: 99%
“…Fifty-two per cent of these respondents indicated that they have already taken action to respond to climate change on their farms. It is clear that farmers from other parts of the country are also beginning to take action in response to climate change (Jemison et al ., 2014; White et al ., 2018; Schattman et al ., 2018 b ) and many farmers anticipate taking action in response to projected changes (Haden et al ., 2012; Niles et al ., 2016; Roesch-McNally, 2018; Roesch-McNally et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%